2012
DOI: 10.1103/physrevb.85.075420
|View full text |Cite
|
Sign up to set email alerts
|

RKKY interaction in disordered graphene

Abstract: We investigate the effects of nonmagnetic disorder on the Ruderman-Kittel-Kasuya-Yoshida (RKKY) interaction in graphene by studying numerically the Anderson model with on-site and hopping disorder on a honeycomb lattice at half filling. We evaluate the strength of the interaction as a function of the distance R between two magnetic ions, as well as their lattice positions and orientations. In the clean limit, we find that the strength of the interaction decays as 1/R 3 , with its sign and oscillation amplitude… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 17 publications
6
44
0
Order By: Relevance
“…These equations indicating ferromagnetic (antiferromagnetic) correlation on same (different) sub-lattice were numerically confirmed with the KPM method [7,8]. We have also checked that the KPM results obtained in the clean limit (see Fig.…”
Section: Numerical Results For the Rkky Exchange Rkky Interaction In supporting
confidence: 52%
See 4 more Smart Citations
“…These equations indicating ferromagnetic (antiferromagnetic) correlation on same (different) sub-lattice were numerically confirmed with the KPM method [7,8]. We have also checked that the KPM results obtained in the clean limit (see Fig.…”
Section: Numerical Results For the Rkky Exchange Rkky Interaction In supporting
confidence: 52%
“…in undoped [7] and doped graphene [8]. They found that for strong enough on-site disorders where Anderson localization takes place, the RKKY interaction exponentially decays with distance which is consistent with the picture based on localized spectrum [9].…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations